2017
DOI: 10.1002/job.2240
|View full text |Cite
|
Sign up to set email alerts
|

The role of self‐regulation in the relationship between abusive supervision and job tension

Abstract: Trait and state self-regulation both have critical influences on workplace behavior, but their influences are thought to operate quite differently. We draw from social exchange and ego depletion theories to investigate the relationship between trait and state self-regulation, as well as how they differentially affect the relationship between subordinates' perceptions of abusive supervision and job tension. Specifically, we examine (a) how the interaction between abusive supervision and trait self-regulation af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 84 publications
1
23
0
Order By: Relevance
“…Self-regulation is generally defined as individuals’ abilities to resist temptation and to calibrate behavior in order to achieve desired goals (Baumeister et al, 2007 ; Lanaj et al, 2014 ), and self-regulation is a useful psychological mechanism that can dictate individuals’ behaviors (or the ability to inhibit unwanted behavioral responses) in both the workplace and the home (Lian et al, 2014 ; McAllister et al, 2018 ; Yam et al, 2016 ). Thus far, research suggests that self-regulation provides mostly beneficial outcomes in the workplace, including increased work performance (Johnson et al, 2014 ), decreased perpetration of bullying behaviors in the workplace (McAllister & Perrewé, 2018 ), and a more robust involvement in helping behavior around the workplace (Trougakos et al, 2015 ).…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…Self-regulation is generally defined as individuals’ abilities to resist temptation and to calibrate behavior in order to achieve desired goals (Baumeister et al, 2007 ; Lanaj et al, 2014 ), and self-regulation is a useful psychological mechanism that can dictate individuals’ behaviors (or the ability to inhibit unwanted behavioral responses) in both the workplace and the home (Lian et al, 2014 ; McAllister et al, 2018 ; Yam et al, 2016 ). Thus far, research suggests that self-regulation provides mostly beneficial outcomes in the workplace, including increased work performance (Johnson et al, 2014 ), decreased perpetration of bullying behaviors in the workplace (McAllister & Perrewé, 2018 ), and a more robust involvement in helping behavior around the workplace (Trougakos et al, 2015 ).…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…Liu et al [71] suggested that representatives may evaluate their business relationships based on the nature of the social exchange with their employees, whose responsibility is to execute work tasks in a manner that is in line with the administration's process [36]. The representative would further cooperate with the senior management team, whose task is to provide vital choices on HR frameworks (e.g., pay circumstances, vocational improvement and representative cooperation approach) [72]. Nonetheless, some front-line managers tend to have close relationships with the floor employees, to ensure that the service delivery meets the organization's required outcomes.…”
Section: Social Exchange Theorymentioning
confidence: 99%
“…Our results provide initial support for a comprehensive model of resiliency and the role of self‐regulation. To confirm these results, however, researchers should conduct additional work using longitudinal methods to assess how activation of self‐regulation affects outcomes (which may even lead to depletion of self‐regulatory resources; McAllister et al, 2018). Future research should also examine training interventions that develop self‐regulation to determine if this improves outcomes.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%